2009
DOI: 10.1016/j.cognition.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Statistical frequency in perception affects children’s lexical production

Abstract: Children’s early word production is influenced by the statistical frequency of speech sounds and combinations. Three experiments asked whether this production effect can be explained by a perceptual learning mechanism that is sensitive to word-token frequency and/or variability. Four-year-olds were exposed to nonwords that were either frequent (presented 10 times) or infrequent (presented once). When the frequent nonwords were spoken by the same talker, children showed no significant effect of perceptual frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 29 publications
7
97
2
1
Order By: Relevance
“…Most relevant to the present study, typically developing children produce non-words with fewer errors when they had heard them spoken by multiple talkers (Richtsmeier et al, 2009). In perception of synthetic speech, listeners generalize better to novel stimuli when their training set is more varied (Greenspan et al, 1988).…”
Section: What Can Acoustic Variability Tell Us About the Nature Of Inmentioning
confidence: 97%
“…Most relevant to the present study, typically developing children produce non-words with fewer errors when they had heard them spoken by multiple talkers (Richtsmeier et al, 2009). In perception of synthetic speech, listeners generalize better to novel stimuli when their training set is more varied (Greenspan et al, 1988).…”
Section: What Can Acoustic Variability Tell Us About the Nature Of Inmentioning
confidence: 97%
“…McMurray (2009, 2010) showed that non-contrastive talker variability helped 14-month-olds distinguish highly-similar words in a word learning task. Richtsmeier, Gerken, Goffman, and Hogan (2009) found that preschoolers more accurately imitated nonsense words when they were heard in a variety of voices. In addition to these acoustically/phonetically-driven effects, preschool-aged and older children seem to draw semantic information from talker variation.…”
Section: Development Of Talker Processingmentioning
confidence: 99%
“…These are listed in Appendix Table 1A. Previous studies have demonstrated that multiple talkers compared to single talkers facilitate word learning (Richtsmeier, Gerken, Goffman, & Hogan, 2009;Rost & McMurray, 2009. Motivated by these findings, the auditory material in the two familiarization phases were recorded by two different talkers, both of whom were native speakers of Russian.…”
Section: Phase I Familiarization Stimulimentioning
confidence: 99%